Pre-service teachers’ perspectives on the use of Wordwall in vocabulary teaching - Annisa, Icha Setiya; Kalisa, Pasca (Universitas Negeri Semarang, 2025)
This study examines prospective English teacher students' perspectives on the use of Wordwall in vocabulary learning. The selection of Wordwall was based on its ability to provide interactive and varied features that are effective in increasing student engagement. The focus on vocabulary learning reflects its vital role in developing overall language proficiency. The research participants were prospective teachers who were in the transition phase between learning and teaching practice, enabling them to share informed reflections on the use of digital media. Using a descriptive qualitative approach, data were collected through semi-structured interviews with final-year students who had experience using or observing the use of Wordwall during teaching practice. The results of the study indicate that Wordwall is perceived as an engaging, interactive, and easy-to-use learning platform that can increase student participation and encourage teacher creativity. The findings also show that Wordwall facilitates the design of more diverse and enjoyable learning activities while strengthening pedagogical skills relevant to the demands of 21st-century education. Wordwall also contributes to the professional development of prospective teachers by providing opportunities to explore digital media and reflect on their teaching practices. These findings contribute significantly to the development of teacher education curricula, particularly in the integration of digital media for effective vocabulary teaching.